Patharian Movement Workshop: Development of Environmentally Friendly Crafts as an Effort to Conserve Black coral - Tapilatu, Julia Rosemary; Siburian, Rima H S; Tapilatu, Maryrose Easter (Sangia Research Media and Publishing, 2025)
Black coral / Antipatharia is one of the colonial marine organisms that has an important ecological role as a habitat provider for various types of animals in the coral reef ecosystem. Currently the existence of black corals has been hunted by coastal communities and sent to various regions in Indonesia and abroad to meet market needs as medicinal ingredients, basic materials for crafts, and amulets. In relation to this, this activity and research was conducted to increase public understanding of the ecological role of black coral for marine ecosystems, provide alternative solutions for the development of environmentally friendly handicrafts as a substitute for accessories made from black coral, and support efforts to develop environmentally friendly handicraft businesses in communities around the Manokwari coastal area. Data collection for workshop activities was carried out in two types, namely: descriptive (data on collaborators and media partners, activity participant data, activity implementation agenda) and qualitative (survey results of general public knowledge related to black coral and evaluation results of workshop activities by participants). The implementation of this workshop was successfully carried out for 2 days on October 22-23, 2021, and was attended by 15 participants consisting of youth groups and mothers. The evaluation results showed a positive response from the participants, where most participants gave fair to very good ratings in the evaluation categories: facilities and accommodation activities, content and presentation of workshop materials, and the structure of the implementation of activities.